Improvement of feed efficiency using protected-energy in the ration of ewes - I-W Mathius; Dwi Yulistiani; E Wina; B Haryanto; A Wilson; A Thalib (Indonesian Center for Animal Research and Development (ICARD), 2001)
High producing ewes required high amounts of energy, which can not be met through feeding conventional ration. Therefore, supplementing energy should be done, especially protected-energy. The purpose of this study was to determine the effects of additional of protected fat/energy on the consumption of ration and the performance of ewes and lambs. Thirty-four local ewes were randomly allotted to four levels of by-pass energy groups, in which parts of energy content in the concentrate was replaced with rumen-protected fatty acids in the proportion of 0 (R1), 5 (R2), 10 (R3), and 20% (R4). Consumption, nutrient digestibility and animal performance (ewes and lambs) were determined by standard procedures. Results showed that the daily dry matter intake during pregnancy (g/kg BW0.75) did not differ among diet (72.1 + 2.56). The crude fibre intake varied slightly between treatment (P>0.05), those being slightly lower intake on the highest replacement of energy content in concentrate diet (R4). Dry matter digestibility were 52.4 + 0.24, 52.1 + 0.30; 51.8 +0.28; and 51.3 + 0.81 in groups R1, R2, R3, and R4, respectively, which were non-significantly different from each other. These results confirmed that the by-pass energy sources replacements did not affect rumen fermentation. The same tendency was also found for crude protein digestibility (P>0.05) i.e. 60.1; 61.8; 61.2; and 60.2 for R1, R2, R3, and R4 respectively. The average daily gain of ewes during gestation period was affected (P<0.05) by by-pass energy replacement and the effect was linear with increasing by-pass energy replacement. Significant difference was not found in the total birth weight of lambs and among dietary treatments. Lambs growth rate during the first 8 week of lactation was the highest on ewes fed diet containing the highest amount of by-pass energy sources (R4). It can be concluded that by-pass fatty acids can be used in ewes’ ration without affecting rumen fermentation and gave a positive respons to animal performance. Key words: By-pass energy, ewes ration, gestation and lactating phase